2019
DOI: 10.1111/trf.15442
|View full text |Cite
|
Sign up to set email alerts
|

Is donating blood for the faint of heart? a systematic review of predictors of syncope in whole blood donors

Abstract: BACKGROUND: Adverse events during donation negatively impact the likelihood of subsequent donation. Syncope is a possible complication of blood donation in healthy individuals. This systematic review aims to identify risk factors for syncope in healthy blood donors. STUDY DESIGN AND METHODS: Medline, Embase,Cochrane, CINAHL, Web of Science, Transfusion Evidence Library, and PubMed libraries up to November 2016 were searched. Inclusion criteria were observational and interventional trials, case series including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
(41 reference statements)
0
16
1
Order By: Relevance
“…While first‐time donors are at a greater risk of experiencing a VVR, the implementation of the donor safety strategies was also found to be beneficial for repeat donors. The odds of experiencing a VVR was reduced by 10% in first‐time donors compared to 13% among repeat donors.…”
Section: Discussionmentioning
confidence: 99%
“…While first‐time donors are at a greater risk of experiencing a VVR, the implementation of the donor safety strategies was also found to be beneficial for repeat donors. The odds of experiencing a VVR was reduced by 10% in first‐time donors compared to 13% among repeat donors.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of faint and pre‐faint reactions (anxiety, nervousness, dizziness, sweating, pallor) sometimes called vasovagal reactions, are incompletely understood, with both physiologic factors, such as hypovolemia, and psychologic factors, such as neural mediated reflexes, contributing 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Many mitigation strategies have been implemented by different blood centers to decrease the risk of vasovagal reactions 5 …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed that young age was a risk factor for syncope during and after blood donation in all seven studies reviewed [10]. Previously from our institution, one of the reported risk factors of IR was younger age [11].…”
Section: Discussionmentioning
confidence: 99%